The Influence of Service Standard Operating Procedures (SOP), Competence, Innovation on Public Satisfaction Through Service Quality as an Intervening Variable at the Balai Karantina Pertanian Kelas I Batam - Pardamean H Situmorang; Chablullah Wibisono; I Wayan Catrayasa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of implementing Service Standard Operating Procedures (SOP), Competency and Innovation on Community Satisfaction through Service Quality as an Intervening Variable. The sample for this research was 105 service users of the Balai Karantina Pertanian Kelas I Batam. The technical analysis uses the path analysis method, namely specifi direct effects and specific indirect effects. The results of the research show that Standard Operating Procedures for Services have a direct effect on service quality, competence does not have a direct effect on service quality , innovation has a direct effect on service quality, service quality has a direct effect on community satisfaction, Standard Operational Procedures of Service has a direct influence on community satisfaction, competence has no direct influence on community satisfaction, innovation has a direct influence on community satisfaction, standard operational procedures of service has no effect on public satisfaction through service quality, competence has no direct effect on public satisfaction through service quality, innovation has no direct effect on public satisfaction through service quality.